Comparison of Hemodynamic Stability in Spinal versus General Anesthesia During Lower Abdominal Surgeries - Marriam Bilal, Muhammad Kashan Siddiqui, Ghazia Raza, Arslan Saleem, Mahmood Ahmad Zahid, Maria Aslam (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Lower abdominal surgeries are commonly performed under either spinal anesthesia (SA) orgeneral anesthesia (GA), yet comparative data regarding intraoperative hemodynamic stabilityremain limited. In this randomized controlled study, 160 patients undergoing elective lowerabdominal procedures were allocated to receive SA with 12.5 mg hyperbaric bupivacaine or GAwith propofol-remifentanil maintenance. Primary endpoints included intraoperative mean arterial